University of Oxford RCUK Open Access report 2016-17 - Rumsey, S; McAslan, J; Walsh, M (University of Oxford, 2017)
Created using RCUK/jisc Microsoft Excel spreadsheet template Report submitted to RCUK listing APC charges and other expenses made against the RCUK block grant for 2016/17.